How Does the Five-Day Work Week Impact Labour Productivity? Exploring the Perceptions of Australian Construction Workers - Michelle Turner; Helen Lingard; Payam Pirzadeh (Buildings)
Construction is a long-hours industry in which people often work a six-day week. This research examined the extent to which shifting to a five-day week schedule impacts labour productivity in construction projects. Five construction projects in Australia implemented a five-day weekly schedule. Interviews were conducted with 89 workers across five projects to explore workers’ subjective productivity and reasons for any perceived changes in productivity associated with the modified schedule. Thematic analysis of interview data revealed that, while some workers perceived the five-day week to be less productive, the majority of participants perceived their productivity to be enhanced, due to a variety of health- and work-related factors. In particular, people experiencing a two-day break from work each week indicated they were better rested and more energetic and engaged in their work. Participants also suggested work was better planned in order to manage the five- compared to the six-day week, and quality improvements also reduced re-work. The research concludes that perceived negative impacts on production associated with not working on Saturdays are offset by an increase in productivity arising from improved health and positive work outcomes associated with the five-day schedule.